Analisis Pertanian Kopi Menggunakan Good Agriculture Practices (GAP) Pertanian Kopi di Kabupaten Garut - Nunung Isnaini Dwi Ningsih; Iwan Aminudin; Darkiman Ruminta; Phonika Aryati (Universitas Sebelas Maret, 2025)
Analysis of Coffee Farming Using Good Agricultural Practices (GAP) Coffee Farming in Garut Regency. Good Agricultural Practices, or GAP on Coffee, is a guideline for good and sustainable coffee cultivation. An analysis of coffee farming in Garut Regency was conducted using GAP on Coffee. The purpose of the analysis was to determine the suitability of farming practices with GAP on Coffee. This was a quantitative descriptive study using interviews and observation techniques to collect data. The analysis was conducted on 11 aspects of good coffee cultivation practices, namely selection, suitability, land preparation, shade tree planting, use of high-quality planting materials, seedling production, planting, fertilization, pruning, shade tree management, integrated pest management, and harvesting. The harvesting aspect includes both harvesting and post-harvest handling. The research results indicate that Garut coffee farmers have implemented GAP on Coffee, with 75% of the scope meeting or exceeding the requirements of GAP on Coffee (≥ 60-100%), specifically in fertilization, planting, seedling production, use of high-quality planting materials, shade tree planting, land suitability, and land selection (≥ 80-100%). And the harvesting scope, which includes harvesting (77%) and integrated pest management (78%). However, the scope that does not yet meet the requirements includes land preparation (40%) and shade tree management and pruning (57%). Limited capital, lack of knowledge, and skills are the main constraints. Limited capital, lack of knowledge, and skills are obstacles. Therefore, to meet the requirements of GAP on Coffeefarming in Garut Regency, there needs to be a fertilizer assistance program as well as training and technical guidance, and ongoing education in implementing GAP, one of which can be done by involving cooperatives and farmer groups as assistants.